Hypoglycemia in small-for-gestational-age neonates - Karahasanoğlu, Özlem; Karatekin, Güner; Köse, Rıfat; Nuhoğlu, Asiye (The Turkish Journal of Pediatrics, 1997)
In this prospective study, we investigated the frequency of hypoglycemia and the proper intervals for screening in small-for-gestational-age (SGA) neonates. We determined test-strip blood glucose values at two, three, six, 12, 24 and 48 hours of age in 25 SGA and 16 appropriate-for-gestational-age (AGA) infants who were born after 37 completed gestational weeks at the Obstetrics Clinics of Şişli Etfal Hospital. Serum glucose determination was immediately done if a test-strip value was less than 40 mg/dl. The frequency of hypoglycemia in SGA neonates was significantly higher (p: 0097) than in AGA neonates. The first three hours, the sixth hour and the 48th hour postnatally were the most common hours for encountering hypoglycemia. Clinical signs were not true indicators of hypoglycemia. These data suggest that screening for hypoglycemia in SGA neonates should continue for 48 hours.
Keywords: hypoglycemia; small-for-gestational-age infants